A Study of Allah’s Will from the Perspective of Transcendent Theosophy and Detachment School of Thought - Ali Arshad Riaahi; Zohreh Al-Sadat Nasr (حکمت اسرا)
In Sadr Al-Mote’alehin’s school of thought, Allah’s will is his complete knowledge of the best system and it is one of the attributes of the essence. Allah is the reason for the existence of all the creation and the administration of his will is essential. In contrast to Sadra’s view, the proponents of the detachment school of thought believe that Divine will does not mean knowledge, but a domination and power over doing or not doing something; as a result, it is considered to be one of the active attributes. Such a definition would entail believing that Allah has freewill in whatever He does and, thus, due to His complete power over everything He will be the causing agent too. Among the criticisms that the followers of detachment school of thought have leveled at Mulla Sadra’s view is the one with regard to the meaning of freewill and the necessity of the existence of a cause and effect between Allah and His creations which leads to Allah being the causing agent. In the present paper, Mulla Sadra’s view regarding the Divine will has been contrasted with that of the followers of the detachment school of thought and the problems raised by the followers of the detachment school of thought against Mulla Sadra’s view in this regard have been answered.